Inner bud temperature of' anna' apple trees in relation to varying environmental conditions (2001)
A field experiment was conducted in Paipa (Colombia) to study the effect of environmental varying over inner bud temperature of an 'Anna' apple tree 4 years old growing in tropical highlands. The tree was defoliated and prunned any weeks after harvest. Air temperature and bud temperature were compared. Bud temperature was measured with a fine digital sensor between the bud scales, to measure the air temperature a normal bulb termometer was used. Temperatures were measured during 19 days from 7:00 to 17:30 hours, starting at defoliation day to "green t ip" bud development stage. The outstanding environmental phenomenon (rain, sunny day, wind, cloudy sky, etc.) was registered simultaneous with the air and bud temperature measures and the information was grouped accourding to the environmental phenomenon. Results shaw that bud temperature was 1,49°C over air temperature in the day.No differences in the night between air and bud temperatureswere found. Bud temperature was 0,57°C over air temperature under rain. But by cloudy sky bud temperature was 0,56°C over airtemperature. Bud temperature was 0,87°C over airtemperature under wind conditions. Under sunny days bud temperature was 2,3 "C over air temperature. Temperature differences between budand air temperature were discussed throughout the transpiration, convection and radiation.